Green tea actions on miRNAs expression – An update. (1st June 2023) - Sousa-Filho, Celso Pereira Batista; Silva, Victoria; Bolin, Anaysa Paola; Rocha, Andrea Livia Silva; Otton, Rosemari
Abstract: Compounds derived from plants have been widely studied in the context of metabolic diseases and associated clinical conditions. In this regard, although the effects of Camellia sinensis plant, from which various types of teas, such as green tea, originate, have been vastly reported in the literature, the mechanisms underlying these effects remain elusive. A deep search of the literature showed that green tea's action in different cells, tissues, and diseases is an open field in the research of microRNAs (miRNAs). miRNAs are important communicator molecules between cells in different tissues implicated in diverse cellular pathways. They have emerged as an important linkage between physiology and pathophysiology, raising the issue of polyphenols can act also by changing miRNA expression. miRNAs are short, non-coding endogenous RNA, which silence the gene functions by targeting messenger RNA (mRNA) through degradation or translation repression. Therefore, the aim of this review is to present the studies that show the main compounds of green tea modulating the expression of miRNAs in inflammation, adipose tissue, skeletal muscle, and liver. We provide an overview of a few studies that have tried to demonstrate the role of miRNAs associated with the beneficial effects of compounds from green tea. We have emphasized that there is still a considerable gap in the literature investigating the role and likely involvement of miRNAs in the extensive beneficial health effects of green tea compounds already described, indicating miRNAs as potential polyphenols' mediators with a promising field to be investigated. Graphical abstract: Image 1 Highlights: Green tea polyphenols act by changing miRNAs expression. miRNAs can be mediators of the effects of polyphenols in green tea. Relationships between green tea polyphenols and miRNAs are sparse in the literature. Studies are needed to understand the relationship between polyphenols and miRNAs.